Castle Redstone - Chadda, Sarwat (Minecraft, 2022)
"Three down-on-their-luck adventurers seek a lost civilization in this Minecraft novel. Rajah would do anything to be a great adventurer. But how can he, when his father's already triumphed over every adventure he can think of? Lord Maharajah fought the Ender Dragon, charted the Overworld, and built a grand manor house. Rajah is surrounded by hand-me-downs, from his father's fancy old name to his fancy old sword. Rajah, Pal, and Faith find a map that leads to the one place Lord Maharajah never conquered--Castle Redstone. The three must trek through perilous swamps, climb high mountains, and discover their true worth to reach their distant destination."--